2010
DOI: 10.1159/000320231
|View full text |Cite
|
Sign up to set email alerts
|

Mugwort-Sensitized Individuals from North Europe, South Europe and North America Show Different IgE Reactivity Patterns

Abstract: Background: Sensitization to weed pollen allergens at the molecular level is not fully understood. We studied IgE reactivity to the major mugwort allergen Art v 1 in relation to allergens from other weed pollen and cross-reactive components in mugwort-sensitized subjects. Methods: Art v 1 and Amb a 1 were affinity purified and coupled to experimental ImmunoCAP® tests. Samples from North Europe (n = 50), South Europe (n = 19) and North America (n = 41) were analyzed for IgE against mugwort pollen, weed allergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
30
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 58 publications
(57 reference statements)
3
30
0
2
Order By: Relevance
“…Art v 1 is a major allergen with a prevalence of sIgE in 79-95% of mugwortallergic patients in previous studies [9,10]. The present study showed that 82% of Art v-positive patients were positive to Art v 1, which is in agreement with the 84% of the recently reported Art v 1 prevalence in the mugwort-sensitized subjects from northern Europe [11]. No Art v1-positive but Art v-negative patients were found in this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Art v 1 is a major allergen with a prevalence of sIgE in 79-95% of mugwortallergic patients in previous studies [9,10]. The present study showed that 82% of Art v-positive patients were positive to Art v 1, which is in agreement with the 84% of the recently reported Art v 1 prevalence in the mugwort-sensitized subjects from northern Europe [11]. No Art v1-positive but Art v-negative patients were found in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Specific IgE to profilin (rCor a 2) is found in 40-45% of hazelnutallergic patients [20]. Also, 52.7% of patients with IgE to crude Parietaria pollen extract had sIgE to profilin (Phl p 12) [21] and 34% of peach-allergic patients had a positive IgE response to birch profilin (rBet v 2) [11]. A recent multicenter study showed that 32% of mugwort sensitization subjects from northern Europe, 16% from southern Europe, and 32% from North America were sensitized to profilin Bet v 2.…”
Section: Discussionmentioning
confidence: 99%
“…Des tests cutanés et des tests de provocation nasale ont démontré son activité biologique in vivo chez des patients allergiques à l'armoise [56]. Les prévalences de sensibilisation à Art v 1 peuvent être variables selon l'origine géographique des patients ; en Europe, elles sont élevées, se situant entre 80 et 90 % [57][58][59][60]. Elles ont également été étudiées récemment en Amérique du Nord [60,61] et en Chine [62] ; Art v 2 a un poids moléculaire de 35 kDa ; Art v 3 est une LTP d'un poids moléculaire de 13 kDa.…”
Section: Les Allergènes [54]unclassified
“…Les prévalences de sensibilisation à Art v 1 peuvent être variables selon l'origine géographique des patients ; en Europe, elles sont élevées, se situant entre 80 et 90 % [57][58][59][60]. Elles ont également été étudiées récemment en Amérique du Nord [60,61] et en Chine [62] ; Art v 2 a un poids moléculaire de 35 kDa ; Art v 3 est une LTP d'un poids moléculaire de 13 kDa. C'est un allergène qui peut être considéré comme majeur car il peut être reconnu par plus de 80 % des sujets allergiques à l'armoise [54].…”
Section: Les Allergènes [54]unclassified
“…In a large number of cases, the positive skin test to plantain corresponds to cross-reactivity with grass group 5 allergens [9] , a situation in which demonstration of specific anti-Pla l 1 IgE could be particularly useful [10] . Mugwort pollen allergy might also be overdiagnosed since positive test results may evolve due to cross-reactivity to other weeds [11] .…”
mentioning
confidence: 99%